Melaksanaan Pembelajaran Kelas Rangkap Secara Efektif - Ayu Arinda; Aziyatun Adinda Fitria; Dwi Ratna Asih; Nadia Ayu Nurjanah; Putri Wulandari Dwi Yovan; Rifki Zibral Mahardika (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
Multi-grade learning is one of the solutions implemented in primary schools, especially in remote, rural and 3T (frontier, outermost, underdeveloped) areas, due to limited teaching staff and infrastructure. In practice, this learning presents its own challenges, both for teachers and students. However, with the right strategies and approaches, multi-grade learning can be effective and provide space for the growth of creativity, independence and cooperation between students across classes. This article aims to examine the effective implementation of multi-grade learning through a qualitative approach with a literature study method. Data are obtained from various literature sources, such as books, scientific journals, and relevant previous research results. The results show that multi-grade learning is effective in limited areas when supported by teacher competence, appropriate learning media, and thematic and collaborative strategies. Approaches such as peer tutoring and integration of local values improve student engagement and learning outcomes.